Developing digital fluency through ubiquitous mobile devices: Findings from a small-scale study - Wang, RuoLan; Wiesemes, Rolf; Gibbons, Cathy (Computers and education, 2012)
As part of the Visual Learning Lab’s initiative of promoting visual learning supported through technologies in Higher Education, this VLL funded study explored part-time mature doctoral students’ use and perceptions of a mobile device in support of their research activities. The study was conducted by the Graduate School in collaboration with the School of Nursing at the University of Nottingham. Six students participated in the study for a period of six months. The methodology was qualitative and included semi-structured exit interviews. By re-analysing the original study ( Gibbons, 2009), this paper raises a vital question about what constitutes a meaningful mobile learning experience which takes into account the different biographical and life stage factors. It challenges the ongoing debate on generational issues on uses of mobile or other digital technologies and leads to discussion of the concept of digital fluency with all learners. ► Using ‘digital fluency’ to understand learner’s engagement with technologies. ► Learning always takes place in complex ‘live’ contexts. ► The variable contexts have impact on user’s appropriation and uses of technologies. ► Research methods and epistemologies should value participation and reflexivity.